THE IMPACT OF COVID-19 ON SPORT ORGANIZATIONS IN CARAȘ-SEVERIN COUNTY - BICHESCU, Andrade-Ionuț; CĂRĂBAŞ, Ionică; GUŞE, Veronica-Mihaela (Studia Universitatis Babeş-Bolyai Educatio Artis Gymnasticae, 2021)
Background: The beginning of 2020, more precisely the month of March, when the Covid-19 pandemic was declared, represents the beginning of one of the darkest pages in the history of world sport. The reason is a well-known one, namely the fact that the implementation of measures to prevent the spread of the SARS-CoV-2 virus have led to the cessation of competitions and the training process, for certain periods of time, in almost all sports. The aim of this study was to see how these measures have influenced the sports activity in Romania, especially that of the sports organizations from Caraş-Severin County (C-S). Thus, a number of 43 sports organizations from CS County were targeted, of which 39.3% being clubs/associations that work only at the level of children and juniors, 12.5% are clubs/associations that have only senior team, and 48.2% are clubs/associations that have both senior team and children/junior teams. All participants agreed that information could be processed and used for scientific purpose, and the study has obtained Research Ethics Approval from The Scientific Council of the Babeș-Bolyai University of Cluj-Napoca. Methods: An online questionnaire survey was conducted, with 31 items, which aimed to outline an accurate picture of the existing situation among sports organizations, which was the situation of sports competitions in 2020, respectively the 2019-2020 season, which was the situation of the training process in the 10 pandemic months of 2020, but more importantly, what are the current situation of the training process and that of the competitive system. Results: Compared to the sports activity carried out at the level of CS county, a number of 8 team sports and a number of 12 individual sports were taken into account, the answers offered being in proportion of 73% from the coaches from team sports, and 27% from individual sports coaches. It was observed that in team sports 78% of the respondents showed that the 2020-2021 competitive season had not yet started until January 2021, while 14.6% it started and was interrupted. Only 7.3% of the teams are in full competition season, the 2020-2021 championship not being embodied due to the Covid-19 pandemic. It was also found that after the resumption of stopped training, as a result of the application of measures to prevent the spread of the pandemic, the number of children decreased both in individual sports and team games. Conclusion: Based on the results, we can see the negative impact of sports organizations that are in the lower leagues, as well as those that are at the level of children and juniors. The fact that training has not been resumed, the measures imposed by the pandemic, the fear induced by a possible infection with the SARS-CoV-2 virus can cause the disappearance of a significant number of sports organizations, which will have a negative effect not only on the performance sport, but also on the level of public health. REZUMAT. Impactul covid-19 asupra antrenamentului în organizațiilor sportive din județul Caraș-Severin. Introducere: Începutul anului 2020, mai exact luna martie, atunci când a fost declarată pandemia de Covid-19, repre¬zintă debutul uneia dintre cele mai negre pagini din istoria sportului mondial. Motivul este unul arhicunoscut şi anume, implementarea unor măsuri de preve¬nire a răspândirii virusului SARS-CoV-2 au determinat sistarea competiţiilor şi a procesului de antrenament, pentru anumite perioade de timp, în aproape toate ramurile sportive. Tocmai pentru a vedea modul în care aceste măsuri au influenţat activitatea sportivă din România, în special cea a organizaţiilor sportive din judeţul Caraş-Severin (C-S), a fost iniţiat acest studio. Astfel, au fost vizate un număr de 43 de organizații sportive care își desfășoară activitatea în județul C-S, dintre acestea 39,3% fiind cluburi/asociații care activează doar la nivel de copii și juniori, 12,5% sunt cluburi/asociații care au doar echipă seniori, iar 48,2% sunt cluburi/asociații care au atât echipă seniori, cât și echipe de copii și juniori. Metode: A fost realizat o anchetă pe bază de chestionar online, cu 31 de itemi, care a urmărit conturarea unei imagini cât mai exacte a situaţiei existente în rândul organizaţiilor sportive, care a fost situaţia competiţiilor sportive în anul 2020, respective sezonul 2019-2020, care a fost situaţia pro¬cesului de antrenament în cele 10 luni pandemice din anul 2020, dar şi mai important, care sunt situaţia actuală a procesului de antrenament și cea a sistemului competițional. Rezultate: Raportat la activitatea sportivă desfăşurată la nivelul județului C-S au fost avute în vedere un număr de 8 sporturi de echipă și un număr de 12 sporturi individuale, răspunsurile oferite fiind în proporție de 73% de la antrenorii de la sporturile de echipă, iar 27% de la antrenorii de la sporturi individuale. S-a putut observa că la sporturile de echipă 78% dintre respondenți au arătat că sezonul competițional 2020-2021 încă nu începuse până în luna ianuarie a anului 2021, iar pentru 14,6% a început și a fost întrerupt. Doar 7,3% dintre echipe sunt în plin sezon competițional, campionatul 2020-2021 neîntrupându-se din cauza pandemiei de Covid-19. De asemenea, s-a putut constata că după reluarea antrenamentelor sistate, ca urmare a aplicării măsurilor de prevenție a răspândirii pandemiei, numărul de copii a înregistrat o scădere atât la nivelul sporturilor individuale, cât şi la jocurile de echipă. Concluzii: Ca urmare a rezultatelor se poate constata pericolul în care se află organizaţiile sportive care îşi desfăşoară activitatea în ligile inferioare, precum şi cele care activează la nivel de copii şi juniori. Faptul că nu au mai fost reluate antrenamentele, măsurile de prevenire a răspândirii pandemiei, teama indusă de o posibilă infectare cu virusul SARS-CoV-2 poate cauza dispariţia unui număr important de organizaţii sportive, ceea ce va avea un efect negativ nu doar asupra sportului de performanţă, ci şi asupra nivelului de sănătate publică. Cuvinte-cheie: cluburi sportive, pandemie Covid-19, antrenament, competiție, lockdown.